2019
DOI: 10.3390/jcm8060770
|View full text |Cite
|
Sign up to set email alerts
|

Use of Secukinumab in a Cohort of Erythrodermic Psoriatic Patients: A Pilot Study

Abstract: Erythrodermic psoriasis (EP) is a dermatological emergency and its treatment with secukinumab is still controversial. Furthermore, no data exist regarding the prognostic value of drug abuse in such a condition. We performed a multi-center, international, retrospective study, enrolling a sample of EP patients (body surface area > 90%) who were treated with secukinumab (300 mg) during the study period from December 2015 to December 2018. Demographics and clinical data were collected. Drug abuses were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…The role of lifestyle and the environment is suggested as modulators of the efficacy of psoriasis treatments. Abuse of alcohol, cannabis, and tobacco affects the treatment response of biologics in psoriasis [ 32 ]. Evidence regarding the effects of the environmental contaminant TCDD via AHR activation on the pathogenesis of psoriasis has accumulated [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of lifestyle and the environment is suggested as modulators of the efficacy of psoriasis treatments. Abuse of alcohol, cannabis, and tobacco affects the treatment response of biologics in psoriasis [ 32 ]. Evidence regarding the effects of the environmental contaminant TCDD via AHR activation on the pathogenesis of psoriasis has accumulated [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bertelsen et al 22 found that IκBζ (NFKBIZ) plays a key role in the efficacy of secukinumab. Smoking and drinking alcohol may affect the efficacy of secukinumab for EP 23 . Personalized plans can be created according to patient characteristics to ensure drug retention rates and reduce adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Secukinumab is a human IgG monoclonal antibody that selectively binds to the interleukin 17A (IL‐17A) inhibiting the releasing of proinflammatory cytokines and chemokines, and its efficacy in the treatment of EP has been reported in several cases 26,29,30 . A recent pilot study evaluated the use of secukinumab in 13 EP patients: 10 of them were responders at week 52 and achieved PASI 90 or PASI 100 without recurrence or adverse reactions 34 . Regarding dialyzed EP patients, only one case has been reported, in a dialyzed 61‐years‐old Japanese female, who developed the erythroderma after discontinuation of the topical steroid therapy, successfully treated with secukinumab 32 .…”
Section: Discussionmentioning
confidence: 99%